2020
DOI: 10.3390/foods10010061
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Wild Plants in Feeding Humanity: A Meta-Analytic Ethnobotanical Approach in the Catalan Linguistic Area

Abstract: Wild food plants (WFP) have always been present in our kitchen, although they have not always been given the same importance as crops. In the Catalan linguistic area (CLA), covered in this paper, WFP were of great importance as a subsistence food not only during the years of the Spanish civil war (1936–1939) and World War II (1939–1945), but also long before these periods and in the years thereafter. The CLA has been well studied at the level of traditional knowledge on plant biodiversity, and much of this inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 62 publications
2
11
0
1
Order By: Relevance
“…These values are consistent with those of other Italian regions (range 5.4-11%) for seasonings only [48], or different areas of the Iberian Peninsula (range 5.05-29.01%) for all food and medicinal uses [49]. Recently, Gras et al [44] have reported that 6.62% of the total native flora in the Catalan linguistic area has a traditional food use. Moreover, our results provide a relevant and novel contribution to the knowledge of food plants in Tuscany and in Italy by including original data from graduation theses.…”
Section: General Datasupporting
confidence: 86%
See 1 more Smart Citation
“…These values are consistent with those of other Italian regions (range 5.4-11%) for seasonings only [48], or different areas of the Iberian Peninsula (range 5.05-29.01%) for all food and medicinal uses [49]. Recently, Gras et al [44] have reported that 6.62% of the total native flora in the Catalan linguistic area has a traditional food use. Moreover, our results provide a relevant and novel contribution to the knowledge of food plants in Tuscany and in Italy by including original data from graduation theses.…”
Section: General Datasupporting
confidence: 86%
“…Tardìo et al [42] in their review reported the use of 419 edible species for the whole of Spain. In the northwestern region of the Iberian Peninsula, Pardo-de-Santayana et al [43] mentioned the use of 97 wild food species while Gras et al [44] reported 278 taxa (beverage excluded) for the Catalan linguistic area. In their comparative analysis on the wild food plants gathered in the Mediterranean Basin, Leonti et al [45] identified 84 species for Italy (Castelmezzano in Basilicata and Gallicianò in Reggio Calabria), 147 for Greece (mostly Crete) and 173 for Spain (Cuenca, Albacete, and Murcia provinces).…”
Section: General Datamentioning
confidence: 99%
“…All EO-based MEs included in the current bioprospecting study exhibit the prevailing phytochemical EO profile for the respective plant taxa. This fact enhances the replicability and upscale of the findings, since the exploited raw materials are widely available in nature [34,[45][46][47][48][49][50]95,96]. In addition, we expect our results to have bearing on the control and the integrated pest management of stored-product insect pests.…”
Section: Discussionmentioning
confidence: 54%
“…For this purpose, EO-based MEs have been implemented for first time as grain coating agents. The subjects of investigation were retrieved from the Greek biodiversity pool with a distinct focus on edible and/or culinary plants [45][46][47][48][49][50]. This way, the EO-based ME grain coating will be compatible with human consumption.…”
Section: Introductionmentioning
confidence: 99%
“…A més, a partir de les dades que conté, permetrà aprofundir sobre aspectes concrets de la investigació en etnobotànica que ofereixen resultats prometedors. A part de detectar buits que cal cobrir en l'inventari etnoflorístic, permetran fer diversos tipus d'estudis metanalítics que fins ara han estat rars en aquesta disciplina, no només als Països Catalans, sinó en general: Pel que fa a l'àrea aquí considerada, el domini lingüístic català, en podem esmentar algun exemple: l'anàlisi de les formes vitals de les plantes i dels territoris fisiogràfics on creixen (Gras et al, 2020b), l'estudi comparatiu de les plantes alimentàries silvestres (Gras et al, 2021a) i el paper de les famílies botàniques en l'etnobotànica mèdica (Gras et al, 2021b). Finalment, faran possible obtenir fàcilment informació sobre molt diversos tipus d'usos de plantes a institucions o empreses interessades a desenvolupar productes comercials d'origen vegetal en camps ben diversos, començant per la farmàcia i l'alimentació, però ni de bon tros aturant-s'hi.…”
Section: Conclusion I Perspectives De Futurunclassified